2020
DOI: 10.1021/acs.iecr.9b06464
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Active Ni Sites in Ternary Layered Double Hydroxide Nanosheets for a Highly Selective Photoreduction of CO2 to CH4 under Irradiation above 500 nm

Abstract: Reduction of photocatalytic CO 2 into renewable hydrocarbon solar fuels is considered to be a promising strategy that can simultaneously address global energy needs as well as environmental concerns. To date, making use of a higher wavelength for photocatalytic conversion of CO 2 to CH 4 continues to be highly challenging. In this work, we report a highly selective reduction of CO 2 into CH 4 and CO by introducing Ni species into CoFe-layered double hydroxide (LDH) as the visible light photocatalyst in conjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 54 publications
(69 reference statements)
2
41
0
Order By: Relevance
“…[ 4–6 ] In recent years, photocatalysts have been widely considered as energy harvest antennas for renewable energy conversion. [ 7–12 ] Driven by solar energy, photocatalytic nitrogen (N 2 ) reduction paves a green and sustainable avenue to the synthesis of NH 3 under mild reaction conditions. [ 13–16 ] Due to the extremely stable NN triple bonds of N 2 molecules with the bond energy of 941 kJ mol −1 , efficient activation of N 2 molecules over catalysts is generally regarded as the bottleneck toward N 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–6 ] In recent years, photocatalysts have been widely considered as energy harvest antennas for renewable energy conversion. [ 7–12 ] Driven by solar energy, photocatalytic nitrogen (N 2 ) reduction paves a green and sustainable avenue to the synthesis of NH 3 under mild reaction conditions. [ 13–16 ] Due to the extremely stable NN triple bonds of N 2 molecules with the bond energy of 941 kJ mol −1 , efficient activation of N 2 molecules over catalysts is generally regarded as the bottleneck toward N 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other MAl‐LDH photocatalysts (M=Mg 2+ , Ni 2+ , and Zn 2+ ), the CoAl‐LDH (containing low spin Co 2+ , t 2g 6 e g 1 ) showed highest activity (43.73 mmol g −1 h −1 ) to generate CO under λ=600 nm irradiation (Figure 3c) [18a] . Recently, our group also found the selectivity of CH 4 improved from 0% (CoFe‐LDH) to 56.6% (NiCoFe‐LDH) by incorporating the Ni species into the CoFe‐LDH layers, indicating the Ni sites plays as the active sites to produce CH 4 in this photocatalytic system [18b] . As such, the understanding of morphology and composition in LDHs‐based catalysts plays a vital role in exploring the active sites and mechanism of CO 2 PR.…”
Section: Morphology and Compositionmentioning
confidence: 63%
“…Recent studies indicated that the defective LDH photocatalysts with various defects showed great potential to achieve outstanding activity of CO 2 PR [18b,46] . Various synthetic methods (such as: the controlling of thickness or size, high temperature treatment, chemical etching, plasma etching, doping et al .)…”
Section: Defect Structurementioning
confidence: 99%
“…Similarly, when Ni 2+ was introduced into CoFe‐LDH, multi‐vacancies were created. PL spectroscopy, photocurrent, and electrochemical impedance spectroscopy (EIS) measurements evidenced that Vo and metal vacancies in LDH nanosheets enhanced the separation and mobility efficiency of photogenerated carriers 52 . Dong et al demonstrated the partial substitution of Mg 2+ by Ni 2+ in MgAl‐LDH nanosheets signally ameliorated their photocatalytic activity for NO removing.…”
Section: Construction Of Efficient Ldh‐based Photocatalystsmentioning
confidence: 99%